THE RELATIONSHIP BETWEEN GOVERNMENT SPENDING AND NIGERIA'S ECONOMIC GROWTH: VECTOR AUTO-REGRESSION APPROACH - Benedict Azu; Agbobu Shedrack Onyeka (International Studies Journal)
This study examined the relationship between government spending and Nigeria's economic growth using time series data from 1982 to 2022. Both the pairwise causality test and the Vector Auto-regression (VAR) model were used. According to the study, government spending on health and education has little effect on economic growth. It also turned out that the effect of public debt on economic growth is negligible. Consequently, the study suggests that: Government should minimise the incidence of borrowing, particularly since 92% of revenue is currently being used to service debt for mostly non-productive borrowings; Government spending in health and education should be increased significantly to at least match regional and global expenditure benchmarks. The debt to GDP ratio is not comprehensive, hence borrowing analysis should also include revenue-generating potential.